2021
DOI: 10.1371/journal.pone.0252831
|View full text |Cite
|
Sign up to set email alerts
|

Main characteristics of dermatoglypics associated with schizophrenia and its clinical subtypes

Abstract: Dermatoglypic patterns are extensively investigated to apply in disease-related risk assessment due to an obvious association between morphological and genetic characteristics. In the current study, we aimed to determine whether the fingerprint and palmar patterns vary between case population with schizophrenia and general population. A cross sectional study was conducted in people diagnosed with schizophrenia (cases) and a control population between 2016 and 2019. In this study, 252 people were participated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…On the one hand, we describe that the rs2023239-G allele is associated with higher PII, which means that this allele, observed in less frequency in patients than in controls in our sample, is in turn related to higher dermatoglyphic complexity as represented by the presence of whorls and loops patterns, figures with more triradii. These results align with previous data reporting lower finger dermatoglyphic patterns complexity assessed through the frequency of the fingertip figures in schizophrenia and schizotypal traits (Chok et al, 2005; Arunpongpaisal et al, 2011; Norovsambuu et al, 2021). On the other hand, studies assessing TABRC as a developmental biomarker evidenced ridge count reductions in patients with schizophrenia and with SSD, as well as in subgroups of patients with reported perinatal complications (Fearon et al 2001; Fañanas et al, 1996; Bramon et al, 2005; Fatjó-Vilas et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…On the one hand, we describe that the rs2023239-G allele is associated with higher PII, which means that this allele, observed in less frequency in patients than in controls in our sample, is in turn related to higher dermatoglyphic complexity as represented by the presence of whorls and loops patterns, figures with more triradii. These results align with previous data reporting lower finger dermatoglyphic patterns complexity assessed through the frequency of the fingertip figures in schizophrenia and schizotypal traits (Chok et al, 2005; Arunpongpaisal et al, 2011; Norovsambuu et al, 2021). On the other hand, studies assessing TABRC as a developmental biomarker evidenced ridge count reductions in patients with schizophrenia and with SSD, as well as in subgroups of patients with reported perinatal complications (Fearon et al 2001; Fañanas et al, 1996; Bramon et al, 2005; Fatjó-Vilas et al, 2008).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have provided insights into the average ridge count distribution among different ngers, indicating that the right and left thumbs typically exhibit the highest mean ridge count (Adamu et al, 2022). However, when assessing the mean ridge count across all ten ngers of schizophrenia patients and healthy volunteers, statistical analysis did not reveal signi cant differences (Norovsambuu et al, 2021). In our study, ridge counts were separately assessed for the radial and ulnar sides of the pulp region of the right and left second and fourth ngers in schizophrenia patients and healthy volunteers (Table 4).…”
Section: Discussionmentioning
confidence: 63%
“…Further analysis based on gender revealed that male schizophrenia patients had an increased frequency of arch patterns and a decreased frequency of whorls when compared to females ( Shakibaei et al, 2011). Additionally, another study reported a higher proportion of whorl patterns among schizophrenia patients when compared to healthy volunteers (Norovsambuu et al, 2021). These ndings underscore the variability in ngertip pattern distributions across different populations and studies, emphasizing the need for cautious interpretation of ngertip pattern association results.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, schizophrenia is often accompanied by comorbidities such as depression, anxiety, sleep, circadian rhythm disorders ( 7 ), and even suicidal tendencies in patients. Patients with schizophrenia comorbidity may suffer from physical health problems, including skin disorders ( 8 ), due to decreased self-care and social isolation. Therefore, schizophrenia has been recognized as a lifelong condition associated with social challenges, constituting a significant global concern ( 9 ).…”
Section: Introductionmentioning
confidence: 99%